UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN CRH BERBANTUAN MEDIA SMARTSHEET PADA SISWA KELAS IV SD - Intan Febiola Kharisma Santi; Elly’s Mersina Mursidik; Rissa Prima Kurniawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Improving Mathematics learning outcomes is essential, as it enhances logical, critical, and systematic thinking. At SDN Grobogan 02, instruction remained teacher-centered and lacked proper use of models and media, leading to low student understanding. This study aimed to improve learning outcomes through the Course Review Horay (CRH) model assisted by Smartsheet. The research used Classroom Action Research (CAR) in two cycles: planning, action, observation, and reflection. The subjects were 20 fourth-grade students. Data collection involved observation, tests, and documentation, using teaching modules, observation sheets, and pre- and post-tests. Results showed improvement: in the pre-cycle, 30% of students achieved the passing score (average 63.25); Cycle I increased to 50% (average 74.5); and Cycle II reached 95% (average 86). These findings confirm that the CRH model with Smartsheet effectively enhances Mathematics learning outcomes